O RELATÓRIO DE UNAMON - Cardoso, Ciro Flamarion (PHOÎNIX, 2020)
This paper contains a translation of an Egyptian text, "The report of Wenamun ", and its analysis. This document is very importantfor three reasons at least. lt has high literary value, using very adequately lhe Late Egyptian language of the Near Kingdom. Moreover; it is lhe sole extant written primary source concerning the exchanges between Egypt and Western Asia in the eleventh century B.C. Finally, in it, for the jirst time in an Egyptian text, the opinions of foreigners, even when opposed to views the Egyptian held, are written down.